Uptake of Covid-19 Preventive Measures Among 10 Immigrant Ethnic Groups in Norway - Abdi Gele; Naima Said Sheikh; Prabhjot Kour; Prabhjot Kour; Samera A. Qureshi (Frontiers Media S.A., 2022)
BackgroundA pessimistic view of the impact of Covid-19 on immigrants has generated an interest in exploring the role of socio-economic and cultural factors on excess infection, hospitalization and death among immigrants. Nowhere in the world is such interest more palpable than in Western countries, including Norway. An expanding amount of literature has demonstrated that preexisting socio-economic inequalities have affected Covid-19 control programs through a disruption of immigrants' uptake to preventive measures. Nonetheless, until very recently, no qualitative research has been conducted to address the impact of socio-economic and socio-cultural factors on immigrants' uptake on preventive measures of Covid-19 in Norway.MethodsAn interview-based qualitative study consisting of 88 participants (49 women and 39 men) from 10 immigrant ethnic groups were carried out. Participants were recruited through purposive sampling and snowballing. In-depth interviews were held through telephone or online for those who have experience in the use of zoom or teams. Data were analyzed using thematic analysis.ResultsWe found that participants' attitudes toward the pandemic in general, and more specifically their adherence to preventive measures, have increased over time. However, the number of barriers that hinder immigrants from adhering to preventive measures were identified and classified more broadly into three main subthemes: (1) socio-economic barriers; (2) socio-cultural barriers, and (3) other barriers. Socio-economic barriers include overcrowded households, working in first-line jobs, education and language. Socio-cultural barriers include collectivist culture, religious fatalism and risk perception toward the pandemic.ConclusionTo reduce the health inequality that arises from overcrowded housing, there is a need for a long-term strategy to help improve the housing situation of low-income immigrant families that live in overcrowded households. In addition, increasing health literacy and more generally, the integration of immigrants, may also reduce the effect of socio-cultural factors on an immigrant's uptake of preventive measures.